The The Effect of Employee Engagement on Job Satisfaction and Organizational Citizenship Behaviour (Ocb) In Employees Bpjs Ketenagakerjaan East Java - Wardhani, Roro; Wulanputih, Tantri; Prihatini, Dewi; Sukarno, Hari (International Journal of Scientific Research and Management (IJSRM), 2020)
An effective way to retain employees is to maintain and foster a harmonious relationship between the organization and its employees. Good treatment of the company to its employees, will form a positive perception in the minds of its employees so that it arises in the name of engagement or employee engagement. Employees who have an attachment to the company will certainly have a sense of job satisfaction. Employee management must be directed to the ability to elevate Organizational Citizenship Behavior (OCB) through the job satisfaction of its employees, this is mainly because of the employee engagement function that provides a set of values ​​for setting company priorities. The problem of employee engagement is essential for a company, because it will always be related to life in the company. The population of this research is all 557 permanent employees in East Java. The sample in this study was selected using the multistage sampling method. After mapping, eight offices were netted, namely Jember, Malang, Mojokerto, Pasuruan, Sidoarjo, Surabaya Karimunjawa, Surabaya Rungkut, and East Java Regional Office as many as 207. The research hypotheses proposed were 2 and were tested using the path analysis method. The conclusion is that employee engagement and job satisfaction partially affect the Organizational Citizenship Behavior (OCB) of East Java BPJS employees and employee engagement has a significant effect on job satisfaction of East Java BPJS Employees. Keywords: employee engagement, job satisfaction, Organizational Citizenship Behavior